Dose-response modeling the risk of carotid bleeding events after stereotactic body radiation therapy for previously irradiated head and neck cancer - Ling, Diane C. (J Radiosurg SBRT, 2019)
Given the lack of clear dose constraints for the carotid artery, we created dose-response models to better quantify the risk of carotid bleeding events following re-irradiation stereotactic body radiation therapy (SBRT) for head and neck cancer (HNC). We performed a retrospective analysis on 75 patients treated with SBRT for recurrent, previously irradiated HNC. Logistic dose-response models were created to predict the risk of a carotid bleeding event, defined as any mucosal bleeding event or bleeding resulting from rupture of the carotid artery or its major branches in the setting of controlled disease. According to the models, the risk of a carotid bleeding event with a cumulative D(0.1cc) of 20 Gy from SBRT is 0.8% (95% CI 0.1%-3.9%), and rises to 5.0% with a D(0.1cc) of 50 Gy. No patient experienced a carotid bleeding event with D(0.1cc) < 39.4 Gy, and none experienced carotid blowout syndrome with a cumulative D(0.1cc) < 47.6 Gy.